Importance of Salmonella Typhi-Responsive CD8+ T Cell Immunity in a Human Typhoid Fever Challenge Model - Fresnay, Stephanie; McArthur, Monica A.; Magder, Laurence S.; Darton, Thomas C.; Jones, Claire; Waddington, Claire S.; Blohmke, Christoph J.; Angus, Brian; Levine, Myron M.; Pollard, Andrew J.; Sztein, Marcelo B. (Frontiers in Immunology, 2017)
Typhoid fever, caused by the human-restricted organism Salmonella enterica serovar Typhi (S. Typhi), constitutes a major global health problem. The development of improved attenuated vaccines is pressing, but delayed by the lack of appropriate preclinical models. Herein, we report that high levels of S. Typhi-responsive CD8+ T cells at baseline significantly correlate with an increased risk of disease in humans challenged with a high dose (~104 CFU) wild-type S. Typhi. Typhoid fever development was associated with higher multifunctional S. Typhi-responsive CD8+ T effector memory cells at baseline. Early decreases of these cells in circulation following challenge were observed in both S. Typhi-responsive integrin α4β7− and integrin α4β7+ CD8+ T effector memory (TEM) cells, suggesting their potential to home to both mucosal and extra-intestinal sites. Participants with higher baseline levels of S. Typhi-responsive CD8+ T memory cells had a higher risk of acquiring disease, but among those who acquired disease, those with a higher baseline responses took longer to develop disease. In contrast, protection against disease was associated with low or absent S. Typhi-responsive T cells at baseline and no changes in circulation following challenge. These data highlight the importance of pre-existing S. Typhi-responsive immunity in predicting clinical outcome following infection with wild-type S. Typhi and provide novel insights into the complex mechanisms involved in protective immunity to natural infection in a stringent human model with a high challenge dose. They also contribute important information on the immunological responses to be assessed in the appraisal and selection of new generation typhoid vaccines.